2015
DOI: 10.1177/1479164114562410
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in the prevalence of metabolic syndrome and cardiovascular-related risk factors in urban adults from 33 communities of China: The CHPSNE study

Abstract: Little is known about the epidemiology of metabolic syndrome in urban areas of China. To estimate the prevalence of MetS and identify its cardiovascular-related factors in men and women, a representative sample of 15,477 urban adults aged 18-74 years in Northeast China was selected from 2009 to 2010. The diagnosis of metabolic syndrome was based on criteria set by the National Cholesterol Education Program/Adult Treatment Panel. The overall prevalence of metabolic syndrome was 27.4% (men 27.9% and women 26.8%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
70
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 37 publications
15
70
2
1
Order By: Relevance
“…People with MS are a susceptible population of many diseases, like type 2 diabetes and cardiovascular diseases23. Sex and age have great influence on the development of MS. MS prevalence increases during aging, but before menopause men have significantly higher MS risk than females, after menopause females have higher MS risk than males456789.…”
mentioning
confidence: 99%
“…People with MS are a susceptible population of many diseases, like type 2 diabetes and cardiovascular diseases23. Sex and age have great influence on the development of MS. MS prevalence increases during aging, but before menopause men have significantly higher MS risk than females, after menopause females have higher MS risk than males456789.…”
mentioning
confidence: 99%
“…However, one research 9 investigated MS prevalence in Korean population; MS was 14.3% for parents and 7.2% for offspring. Song et al 10 studied the MS prevalence in 15.477 individuals from another oriental country, China. They detected a prevalence of 27.4%.…”
Section: Epidemiology Of Metabolic Syndromementioning
confidence: 99%
“…14 Previous Chinese studies 15,16 reported gender-specific correlations between SUA, MetS and CV risk factors. It would be useful to know whether there were such differences in the Song et al 1 study.…”
mentioning
confidence: 99%
“…Song et al, 1 in the May 2015 issue of the journal, comment on gender differences in the associations between the prevalence of metabolic syndrome (MetS) and cardiovascular (CV) risk factors in urban adults from 33 Chinese communities.…”
mentioning
confidence: 99%
See 1 more Smart Citation